2018
DOI: 10.1101/308189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of RNA-seq studies reveals genes responsible for life stage-dominant functions in Schistosoma mansoni

Abstract: Background: Since the genome of the parasitic flatworm Schistosoma mansoni was sequenced in 2009, various RNA-seq studies have been conducted to investigate differential gene expression between certain life stages. Based on these studies, the overview of gene expression in all life stages can improve our understanding of S. mansoni genome biology. Methods: publicly available RNA-seq data covering all life stages and gonads were mapped to the latest S. mansoni genome. Read counts were normalised across all samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Transcript profiling by RNA-seq showed high transcript levels of Sm-tdc in bM compared to sM and no transcripts in bF or sF. The meta-analysis of all life stages showed that Sm-tdc is stage- and gender-specific expressed in males, being significantly up-regulated after pairing (Lu and Berriman, 2018). Similarly, the amount of Sm-ebony transcripts dominated in bM but also in sF, whereas sM and bF showed significantly reduced transcript levels.…”
Section: “Nervous” Male Schistosomementioning
confidence: 99%
See 1 more Smart Citation
“…Transcript profiling by RNA-seq showed high transcript levels of Sm-tdc in bM compared to sM and no transcripts in bF or sF. The meta-analysis of all life stages showed that Sm-tdc is stage- and gender-specific expressed in males, being significantly up-regulated after pairing (Lu and Berriman, 2018). Similarly, the amount of Sm-ebony transcripts dominated in bM but also in sF, whereas sM and bF showed significantly reduced transcript levels.…”
Section: “Nervous” Male Schistosomementioning
confidence: 99%
“…Similarly, the amount of Sm-ebony transcripts dominated in bM but also in sF, whereas sM and bF showed significantly reduced transcript levels. The meta-analysis showed stage-specific expression in adults with a significant up-regulation in bM and sF (Lu and Berriman, 2018). A comprehensive quantitative reverse transcription-PCR analysis with RNA from males after pairing, separation, and re-pairing in vitro finally confirmed the direct influence of pairing on the transcript levels of both genes with a clear bias toward bM (Haeberlein et al, 2019).…”
Section: “Nervous” Male Schistosomementioning
confidence: 99%
“…A recent meta-analysis of published RNA-seq experiments provides a comprehensive view of gene expression changes across all life stages of Schistsoma mansoni (Lu and Berriman 2018). However, as it's not possible to cover all genes in one publication, it's very likely that there are more interesting candidates that were not mentioned in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme domain shows homology with the human ADP ribose (ADPR) pyrophosphatase NUDT9, a feature characteristic of TRMP2 channels [14][15][16][17]. Analysis of Sm.TRPM PZQ in transcriptomic datasets evidences expression across various parasite life cycle stages [18], and analysis of flatworm genomes revealed expression of closely related TRPM channels in both free-living and parasitic flatworms that exhibit sensitivity to PZQ ( Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, consistent with Sm.TRPM PZQ being a target of this clinically important therapeutic, Sm.TRPM PZQ is expressed through various parasite life cycle stages [18] and is present in other flatworms sensitive to PZQ ( Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%